Examining the application of the IDEAL framework in the reporting and evaluation of innovative invasive procedures: secondary qualitative analysis of a systematic review - Richards, Hollie Sarah; Cousins, Sian; Scroggie, Darren L; Elliott, Daisy; Macefield, Rhiannon; Hudson, Elizabeth; Mutanga, Ian Rodney; Shah, Maximilian; Alford, Natasha; Blencowe, Natalie S; Blazeby, Jane (BMJ open, 2024)
ObjectivesThe development of new surgical procedures is fundamental to advancing patient care. The Idea, Developments, Exploration, Assessment and Long-term (IDEAL) framework describes study designs for stages of innovation. It can be difficult to apply due to challenges in defining and identifying innovative procedures. This study examined how the IDEAL framework is operationalised in real-world settings; specifically, the types of innovations evaluated using the framework and how authors justify their choice of IDEAL study design.DesignSecondary qualitative analysis of a systematic review.Data sourcesCitation searches (Web of Science and Scopus) identified studies following the IDEAL framework and citing any of the ten key IDEAL/IDEAL_D papers.Eligibility criteriaStudies of invasive procedures/devices of any design citing any of the ten key IDEAL/IDEAL_D papers.Data extraction and synthesisAll relevant text was extracted. Three frameworks were developed, namely: (1) type of innovation under evaluation; (2) terminology used to describe stage of innovation and (3) reported rationale for IDEAL stage.Results48 articles were included. 19/48 described entirely new procedures, including those used for the first time in a different clinical context (n=15/48), reported as IDEAL stage 2a (n=8, 53%). Terminology describing stage of innovation was varied, inconsistent and ambiguous and was not defined. Authors justified their choice of IDEAL study design based on limitations in published evidence (n=36) and unknown feasibility and safety (n=32) outcomes.ConclusionIdentifying stage of innovation is crucial to inform appropriate study design and governance decisions. Authors’ rationale for choice of IDEAL stage related to the existing evidence base or lack of sufficient outcome data for procedures. Stage of innovation was poorly defined with inconsistent descriptions. Further work is needed to develop methods to identify innovation to inform practical application of the IDEAL framework. Defining the concept of innovation in terms of uncertainty, risk and degree of evidence may help to inform decision-making.